Ethic of the responsibility in the cultural and moral position of modern Russian youth: the transformation of the moral in the complex society - N. N. Zarubina (Vestnik MGIMO-Universiteta)
The author analyses the transformations of the morality in today's complex society. On the example in the changes in value orientations of modern Russian youth is shown that the growth of social irresponsibility is a serious challenge for the country's development.